Case report: An intrauterine device hugging the musculus rectus abdominis through the center of a cesarean scar - Jing, Jigang (Frontiers in Surgery, 2023)
A 34-year-old woman presented with an abscess of the abdominal wall, with a 10-day history of rupture and discharge. She had a history of cesarean section 17 years ago, intrauterine device (IUD) insertion 5 years ago, and intermittent lumbago and abdominal pain for the past 4 years. A V-shaped IUD was observed via ultrasound between the bladder and abdominal wall, clinging to the musculus rectus abdominis through the center of the cesarean scar. Pelvic computed tomography (CT) revealed a V-shaped metal density at the anterior upper edge of the bladder, one end of which seemed to penetrate the abdominal wall. IUD migration was confirmed by surgery 2 days later. The patient recovered after IUD removal. This case affirms that a migrated IUD can lead to serious complications, even if there are no obvious symptoms for many years. Apart from the fact that the IUD has fallen out of place, a migrated IUD should be removed promptly, regardless of obvious complications. Furthermore, regular ultrasound examination is important for early diagnosis of IUD displacement. Based on the relevant literature, we also hypothesize the possible mechanism of IUD migration between the anterior bladder wall and the abdominal wall. Core tip Uterine perforation and IUD migration to the organs in the abdominopelvic cavity are serious complications of IUD insertion. We present a case of uterine perforation complicated by IUD migration with the application of intraoperative ultrasound localization. This case highlights that ultrasound, especially intraoperative ultrasound, can provide objective information for the diagnosis and localization of IUD migration, with the advantages of point of care, real-time imaging, convenience, low cost, and lack of radiation. Based on this case and on the relevant literature, we hypothesized the possible mechanism of IUD migration between the anterior bladder wall and the abdominal wall. To the best of our knowledge, no previous research has discussed the process of IUD migration beyond the anterior wall of the bladder.